بیت المال کا معاصر تصور اور اس کے ذرائع تمویل و مصارف: The modern concept of Bait-ul_Mal and the analysis of its income and outcome sources - Khan, Muhammad Rehan; Shah, Dr. Noor Wali (Al-Irfan, 2024)
Islam proposes the economic and financial model of an Islam state. Through that economic model, Islamic states were run by the the caliphs. It presents the institution of Bait-ul-Mal. The economic condition of Pakistan is declining day by day and the current taxation system is considered as direct responsible to that. The economic system of an Islamic system is run and managed by the institution Bait-ul-Mal that supervise and govern all the income and outcome of the state. The prominent sources of its income and outcome are described in fiqh books in details. It is necessary to review the concept of Bait-ul-Mal in the contemporary world in order to know how it can be implemented in an Islamic country. And it this regard one should know the ansewers to some questions like; what is the model of economic system of an Islamic state? What is Baitul-ul-Mal and what are the sources of income of Bait-ul-Mal? The bigger question come when the application of sources of consumption (Masaarif) is being discussed. To do the analysis of these question, we found that with some changes the concept of Bait-ul-Mal is applicable in the current scenario of an Islamic country. Also there is a room for specified taxes imposed on rich people to fulfill the needs of poor people.